1972
DOI: 10.1063/1.1693983
|View full text |Cite
|
Sign up to set email alerts
|

Internal Rarefied Gas Flows with Backscattering

Abstract: A modification of the boundary condition describing the interaction between a gas molecule and a wall is proposed for use in the calculation of internal rarefied gas flows. The effect of the altered boundary condition on a number of flows of interest is calculated. In several cases, for which experimental data are available, comparison is made between predicted and measured transport. It is found that significant improvement in the predicted transport results from the suggested boundary condition modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…(4), the parameter may take values between 0 and 2, with the upper limit indicating perfect back-reflection. These authors 41,65 (as well as others 25,34 ), found good agreement with experimental data for α > 1, in particular on rough surfaces. However, the values α 2 > 1.4 seen in Table III for Kr, CO 2 , and C 2 H 6 seem rather (and possibly too) high.…”
Section: B Slip and Accommodation Coefficientssupporting
confidence: 70%
See 2 more Smart Citations
“…(4), the parameter may take values between 0 and 2, with the upper limit indicating perfect back-reflection. These authors 41,65 (as well as others 25,34 ), found good agreement with experimental data for α > 1, in particular on rough surfaces. However, the values α 2 > 1.4 seen in Table III for Kr, CO 2 , and C 2 H 6 seem rather (and possibly too) high.…”
Section: B Slip and Accommodation Coefficientssupporting
confidence: 70%
“…For α > 1 (a rare case), a fraction of the molecules is back-reflected with inversion of the lateral and normal momenta. 41 …”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In this model it is supposed that a fraction of molecules f is scattered according to the cosine law and a fraction 1 − f is scattered in the direction opposite to the velocity of incident molecules. In the backscattering model w ¼ f 2Àf [8]. At first, let us consider the diffuse-specular scattering model.…”
Section: Joint Effect Of Surface Diffusion and Character Of Spatial Dmentioning
confidence: 99%
“…It is worth noting that for rough surfaces the backscattering model is used [8]. In this model it is supposed that a fraction of molecules f is scattered according to the cosine law and a fraction 1 − f is scattered in the direction opposite to the velocity of incident molecules.…”
Section: Joint Effect Of Surface Diffusion and Character Of Spatial Dmentioning
confidence: 99%